Healthcare ethics and training concepts, methodologies, tools, and applications (Medical Information Science Reference, 2017)
"This book examines the latest training and ethical issues in the healthcare industry. Including innovative studies on interactive behavioral health, management and supervision, and patient rights, this multi-volume book is an ideal source for professionals, researchers, academics, practitioners, and students interested in the improvement of health literacy"--Provided by publisher.